Qualitative and Quantitative Characteristics of Soil Microbiome of Barents Sea Coast, Kola Peninsula - Maria Korneykova; Dmitry Nikitin; Vladimir Myazin (Microorganisms, 2021)
The soil microbiome of the Barents Sea coast of the Kola Peninsula is here characterized for the first time. The content of copies of ribosomal genes of archaea, bacteria, and fungi was determined by real-time PCR. Reserves and structure of biomass of soil microorganisms such as total biomass of fungi and prokaryotes, length and diameter of mycelium of fungi and actinomycetes, proportion of mycelium in biomass, number of spores and prokaryotic cells, proportion of small and large fungal propagules, and morphology of mycobiota spores were determined. The largest number of ribosomal gene copies was found for bacteria (from 6.47 × 109 to 3.02 × 1011 per g soil). The number of copies of ribosomal genes of fungi and archaea varied within 107–109 copies of genes/g soil. The biomass of microorganisms (prokaryotes and fungi in total) varied from 0.023 to 0.840 mg/g soil. The share of mycobiota in the microbial biomass ranged from 90% to 97%. The number of prokaryotes was not large and varied from 1.87 × 108 to 1.40 × 109 cells/g of soil, while the biomass of fungi was very significant and varied from 0.021 to 0.715 mg/g of soil. The length of actinomycete mycelium was small—from 0.77 to 88.18 m/g of soil, as was the length of fungal hyphae—an order of magnitude higher (up to 504.22 m/g of soil). The proportion of fungal mycelium, an active component of fungal biomass, varied from 25% to 89%. Most (from 65% to 100%) of mycobiota propagules were represented by specimens of small sizes, 2–3 microns. Thus, it is shown that, despite the extreme position on the mainland land of Fennoscandia, local soils had a significant number of microorganisms, on which the productivity of ecosystems largely depends.